Strategies for Developing Responsibility in Early Childhood within Islamic Educational Institutions: A Systematic Literature Review - Lailatul Karomah; Mallevi Agustin Ningrum; Kartika Rinakit Adhe; Ruqoyyah Fitri; Nurul Istiq’faroh (Universitas Al-Amien Prenduan, 2026)
Responsibility character development in early childhood has become an important issue in Islamic education because it is closely related to moral formation, self-regulation, and children’s social readiness. Although studies on Islamic character education have increased, no review has specifically synthesized strategies for developing responsibility in Islamic early childhood education institutions. Therefore, this study analyzes strategies for developing responsibility in early childhood within Islamic educational institutions using a Systematic Literature Review (SLR) approach. The methodology followed the PRISMA 2020 protocol by analyzing 13 selected articles from 542 initial literature sources identified through national and international databases. The findings indicate that responsibility development strategies in early childhood can be classified into four main themes: habituation strategies, reinforcement and direct experience strategies, family roles and parenting patterns, and the cultivation of moral and religious values. Habituation through routine activities, role modeling, and daily discipline emerged as the most dominant approach. Experience-based learning methods, such as project-based learning, cooking classes, storytelling, and token economy, effectively enhance children’s sense of responsibility through active engagement in real-life activities. The findings also reveal that parenting styles, parental involvement, and Islamic school culture significantly influence the formation of children’s responsibility. Furthermore, research in this field demonstrates a paradigm shift from behavioristic approaches to constructivist and socio-emotional approaches that emphasize direct experience, self-regulation, and the internalization of moral and spiritual values.